2017
DOI: 10.1371/journal.pone.0189072
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic profiling and stable isotope labelling of Trichomonas vaginalis and Tritrichomonas foetus reveal major differences in amino acid metabolism including the production of 2-hydroxyisocaproic acid, cystathionine and S-methylcysteine

Abstract: Trichomonas vaginalis and Tritrichomonas foetus are pathogens that parasitise, respectively, human and bovine urogenital tracts causing disease. Using LC-MS, reference metabolomic profiles were obtained for both species and stable isotope labelling with D-[U-13C6] glucose was used to analyse central carbon metabolism. This facilitated a comparison of the metabolic pathways of T. vaginalis and T. foetus, extending earlier targeted biochemical studies. 43 metabolites, whose identities were confirmed by compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…The 2-hydroxy-acid dehydrogenase(s) responsible for the reduction of the 2-keto acids to form lactates has not been identified. In lactic acid bacteria (28) and protozoa, such as Trichomonas vaginalis (29), these reactions are catalyzed by the canonical NAD-dependent hydroxy acid dehydrogenase lactate dehydrogenase (LDH), an enzyme with broad substrate specificity (30). Leishmania species do not encode LDH, but genes for malate dehydrogenases (MDH) and a putative D-lactate dehydrogenase (D-LDH) are present.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-hydroxy-acid dehydrogenase(s) responsible for the reduction of the 2-keto acids to form lactates has not been identified. In lactic acid bacteria (28) and protozoa, such as Trichomonas vaginalis (29), these reactions are catalyzed by the canonical NAD-dependent hydroxy acid dehydrogenase lactate dehydrogenase (LDH), an enzyme with broad substrate specificity (30). Leishmania species do not encode LDH, but genes for malate dehydrogenases (MDH) and a putative D-lactate dehydrogenase (D-LDH) are present.…”
Section: Discussionmentioning
confidence: 99%
“…107,108 A comparison between metabolomic networks of closely related pathogens can also be achieved by stable isotope labelling to understand the functions of enzymes. 109,110 The technique is also applied to investigate the effect of drug candidates and drug combinations for clinical treatment. Cobbold and McConville summarized a mass spectrometrybased protocol for detecting the effects of antimalarial drugs on Plasmodium falciparum, and through its coupling with stable isotope tracing, the method can provide a broader understanding of overall metabolomic perturbations.…”
Section: Metabolomic Flux Studies Using Stable Isotope Tracingmentioning
confidence: 99%
“…Nozaki, Ali [130] reported that the metabolism of sulfur amino acids in T. vaginalis probably influences their virulence and defense against stress. Based on an extensive bioanalytical study, Westrop, Wang [131] showed that there are major differences in cysteine and methionine synthesis and metabolism in T. vaginalis and T. foetus, that both trichomonads synthesize methylthioadenosine by an unusual mechanism, that T. foetus has higher levels of ornithine and citrulline than T. vaginalis and released high levels of the polyamine putrescine, and that T. vaginalis but not T. foetus exported 2hydroxyisocaproic acid derived from leucine. Because these biochemical events and associated enzymes probably contribute to the viability of the protozoa, inhibition of the active sites of the enzymes might transform pathogenic to nonpathogenic trichomonads.…”
Section: Mechanisms Of Anti-trichomonad Effectsmentioning
confidence: 99%
“…vaginalis probably influences their virulence and defense against stress. Based on an extensive bioanalytical study, Westrop, Wang [ 131 ] showed that there are major differences in cysteine and methionine synthesis and metabolism in T . vaginalis and T .…”
Section: Introductionmentioning
confidence: 99%